Basic Principles of Communication - Váradi-Csema, Erika (Interdisciplinary and Child-Friendly Communication, 2025)
The aim of this chapter is to review the concept, meaning, and content elements of communication.The function, characteristics, and main principles of communication are all important for the successful interaction with children and young people and for a better understanding of their communication messages. One of the most important basic principles of communication is that it is impossible not to communicate. Professionals and representatives of authorities send messages to minors who come into contact with, even if adults and experts do not otherwise express themselves verbally. When working with children, it is important to bear this in mind not only to ensure more effective interaction, but also because the child’s behaviour will be a response to the messages sent by professionals through non verbal channels. Creating an atmosphere of trust is an important prerequisite for effective action, regardless of the type of official procedure or role involved. It is also a prerequisite and guarantee for the wider enforcement of children’s rights.Keywords: concept of communication, meaning and content of communication, basic principles ofcommunication